Role of coagulation/flocculation as a pretreatment option to reduce colloidal/bio-colloidal fouling in tertiary filtration of textile wastewater: A review and future outlooks - Aragaw, Tadele Assefa; Bogale, Fekadu Mazengiaw (Frontiers in Environmental Science, 2023)
Textile industry wastewater has become a growing concern in recent years due to it being characterized by a high load of organic dyes, suspended and dissolved solids, alkaline pH, and low biodegradability. For example, TSS in the textile was recorded as from 15 to 8,000 mg/, hence coagulation/flocculation pretreatment process is incredibly important for the textile industry effluents. As a result, environmental authorities necessitate textile industries to treat effluents before discharge into the environment. Tertiary filters, particularly membrane filtrations, are the most preferable process to recover good quality water at the tertiary treatment phase, which feeds from secondary effluents, in wastewater treatment processes. However, fouling is still a challenge due to a higher load of suspended solids, colloids, organic matter, and a high level of bio-colloids (mostly from secondary effluents) in the textile wastewater treatment process. Bio-colloids are any colloidal entities of organic matter including microorganisms and their exudates. Hence, a coagulation/flocculation unit process, as a pretreatment option, is critical both at the primary treatment stage and after secondary (biological) effluents to prevent fouling problems at the tertiary filters. We reviewed identifying major foulants causing tertiary filter damage and available pretreatment option for the removal of these foulants. We focus on and suggest the coagulation/flocculation process as a good pretreatment alternative to prevent filter fouling due to it provides a reliable process to treat high water turbidity that arises from a high load of solids and colloids. Amongst different types of foulants, we focus on and present the colloidal solids and bio-colloidal foulants that could be major causes of fouling. Because these foulants are less understood and expected to be dominant in the textile industry wastewater, as well as established pretreatment alternatives are not well developed for the bio-foulants fed from the secondary effluent. Thus, these foulants need to be critically identified in the textile wastewater treatment plants to integrate suitable pretreatment options to prevent fouling potentiality. We proposed a coagulation/flocculation unit process as a pretreatment option to reduce colloidal and bio-colloidal fouling before the tertiary treatment stage, next to secondary effluent is critical.